Urban Living Lab: An Experimental Co-Production Tool to Foster the Circular Economy - Federico Cuomo (Social Sciences, 2022)
In recent decades; the balance of power between institutional and economic actors has radically changed; with a significant impact on the modes and dynamics of governance. In the broad array of experimental practices of co-production; Living Labs (LLs) represent a promising mode of collaboration among public bodies; research centres; private companies and citizens. By means of LLs; public actors aim to co-produce experimental policies; breaking out of traditional policy schemes to find new solutions to collective problems. On an urban scale; such tools have come to be known as Urban Living Labs (ULLs), and they are increasingly used by local governments to tackle complex problems such us stimulating the circular economy to tackle climate change. This paper provides a systematic review of case studies to understand whether and how the ULLs can represent an effective policy tool to foster the circular economy on an urban scale.